2017
DOI: 10.5796/electrochemistry.85.634
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effects on Methanol Oxidation on Single Crystal Electrodes of Palladium

Abstract: Methanol oxidation reaction (MOR) has been studied on the low index planes of Pd (Pd(111), Pd(100) and Pd (110)) in 0.1 M HClO 4 using voltammogram. Onset potential of methanol oxidation increases as Pd (110)~Pd(100) < Pd(111). The activity for the MOR is estimated using anodic peak current density of the voltammograms. The order of the activity is Pd(111)~Pd(110) B Pd(100): (100) surface enhances the activity for the MOR on Pd electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The anodic peaks observed around 0 V and 0.2 V (vs. RHE) for all of the above catalysts correspond to the hydrogen desorption from the Pd (111) and Pd (100) surfaces [36,37] . The same hydrogen desorption peak feature indicates that all the catalysts own the same surface morphology, and Pd (111) is the dominant phase exposed on the surface, which agrees well with the XRD results.…”
Section: Resultssupporting
confidence: 86%
“…The anodic peaks observed around 0 V and 0.2 V (vs. RHE) for all of the above catalysts correspond to the hydrogen desorption from the Pd (111) and Pd (100) surfaces [36,37] . The same hydrogen desorption peak feature indicates that all the catalysts own the same surface morphology, and Pd (111) is the dominant phase exposed on the surface, which agrees well with the XRD results.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, in the present electrolyte medium (H 2 SO 4 ), deposition of Pt on Pd(111) sites is less probable than on other sites during the short reaction time of 2 min (longer reaction time is avoided to minimize the Pt deposition on carbon support by direct FA oxidation). Figure also shows that the CV of Pd/C has two sharp peaks in the H UPD region, peak I and peak II, apparently corresponding to Pd(111) and Pd(100), whereas H UPD happens on Pd(110) in a wide potential range from 0.02 to 0.3 V RHE . , Interestingly, in the first sweep cycle of Pt@Pd/C/GC, the disappearance of peak II (see Figure ) coincided with the appearance of current peak due to the oxidation of adsorbed CO. Thus, it can be understood that Pd(100) sites are covered by CO-adsorbed Pt.…”
Section: Results and Discussionmentioning
confidence: 74%
“…Figure 2 also shows that the CV of Pd/C has two sharp peaks in the H UPD region, peak I and peak II, apparently corresponding to Pd(111) and Pd(100), whereas H UPD happens on Pd(110) in a wide potential range from 0.02 to 0.3 V RHE . 47,48 Interestingly, in the first sweep cycle of Pt@Pd/ C/GC, the disappearance of peak II (see Figure 2) coincided with the appearance of current peak due to the oxidation of adsorbed CO. Thus, it can be understood that Pd(100) sites are covered by CO-adsorbed Pt.…”
Section: Experimental Methodsmentioning
confidence: 79%
“…To date, many groups have reported the preparation of various Pd polyhedrons with specifically exposed facets: cubes with {100} facets, rhombic dodecahedron with {110} facets, and octahedron with {111} facets ( Figure ) . For instance, Hoshi et al carefully investigated the shape effect of Pd single crystal with different surface structure toward the methanol oxidation reaction (MOR) . Their experiments revealed that the Pd(111) surface showed the lowest activity, while the Pd(100) surface showed the highest activity for MOR.…”
Section: Introductionmentioning
confidence: 99%